Pengaruh Intellectual Capital Disclosure Terhadap Profitabilitas Perusahaan Sektor Pariwisata Dan Perhotelan Di Indonesia - Naomi Lamiki; Victoria Stephanie; Saarce Elsye Hatane (Business Accounting Review, 2021)
This study aims to determine the effect of intellectual capital disclosure, company size, and Debtto Asset Ratio (DAR) on Return on Assets (ROA) in tourism and hospitality companies in Indonesia.The sample used in the study consisted of 31 tourism and hospitality companies listed on the IndonesiaStock Exchange (IDX) with a 5-year observation year spanning 2015 to 2019. Data processing uses Gretlsoftware. This study used a panel data regression analysis method. There are 3 independent variablesin this study with 1 dependent variable. The independent variables in this study are Intellectual CapitalDisclosure, Company Size, Debt to Asset Ratio. Dependent variable in this study is ROA. ICD ismeasured using the average result of three components of intellectual capital, namely human capital,structural capital, and relational capital. There are three hypotheses tested in this study. The results ofthe study found that intellectual capital disclosure had a significant positive effect on ROA. DAR has asignificant negative effect on ROA. Company size does not have a significant effect on ROA.